Pengaruh Kepemimpinan, Struktur Organisasi, Lingkungan Kerja Terhadap Motivasi Kerja, dan Kinerja Karyawan Di PT Tanjung Power Indonesia - Arif Rahmanto; Rizali Hadi; Riza Firdaus (JURNAL BISNIS DAN PEMBANGUNAN, 2023)
In the current era of globalization, there is economic growth that shares a brilliant perspective, for any party or company that can compete with other companies in the same industry, whether it's a product or service business. In addition, the company certainly wants to get optimal results or in other terms wants to benefit from these business activities.In accordance with the circumstances, the company must be able to have the option to adapt to changes. With the changes - changes will directly or indirectly affect the performance of workers and will also affect the state of the company. The influence of a leader's leadership, organizational structure, and work environment is very influential on the performance or work performance of workers is very valuable for a company both internal conditions and external conditions because it will affect the goals of the company's organization. Human resources in an organization must be maintained competently so that equivalence is developed between the wishes of workers and job claims. It is not uncommon for many workers who are actually highly capable of energy, but cannot perform at work, this situation is possible due to work environment factors. It's a shame, a company that has highly skilled workers but can't work usefully.The test result proves that leadership Effect on job performance with the influence of 47,56%, Job Satisfaction has a significant effect on Job Performance with the influence of 42,3% including very enough category, Organization Structure has significant influence of 49,47%, Work environment on job performance of 46,59%, Work Motivation on job Performance of 50.49% Keywords: Leadership, Organizational Structure, Work Environment